2019
DOI: 10.1007/s40261-018-00743-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Off-Label Topical Treatments for the Management of Androgenetic Alopecia: A Review

Abstract: Androgenetic alopecia (AGA) is characterized by non-scarring follicle miniaturization. Despite the success of approved therapies, commonly reported side effects and the need for continual use has led to the investigation of alternative therapies. The aim of this paper is to critically review the success of off-label, topical monotherapies for treatment of AGA in men. A literature search was conducted to obtain randomized, controlled and blinded studies that investigated off-label, topical, monotherapies in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In a recent review of the off-label topical treatments for AGA, it was concluded that prostaglandin analogues and polyphenols, such as latanoprost and procyanidin oligomers respectively, can improve hair growth possibly targeting proposed pathogenetic mechanisms of AGA. 18 AnaGain is another ingredient containing extract of edible organic pea sprouts that are a rich in biotin, L-arginine and isoflavones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review of the off-label topical treatments for AGA, it was concluded that prostaglandin analogues and polyphenols, such as latanoprost and procyanidin oligomers respectively, can improve hair growth possibly targeting proposed pathogenetic mechanisms of AGA. 18 AnaGain is another ingredient containing extract of edible organic pea sprouts that are a rich in biotin, L-arginine and isoflavones.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are few reports on the clinical efficacy of polyphenols among patients with AGA. In a recent review of the off‐label topical treatments for AGA, it was concluded that prostaglandin analogues and polyphenols, such as latanoprost and procyanidin oligomers respectively, can improve hair growth possibly targeting proposed pathogenetic mechanisms of AGA 18 …”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of the off‐label topical treatments for AGA, it was concluded that prostaglandin analogs and polyphenols, such as latanoprost and procyanidin oligomers, respectively, can improve hair growth possibly targeting proposed pathogenetic mechanisms of AGA. In two studies, procyanidin oligomers showed greater efficacy over the vehicle with response to mean change in hair density at week 24 ( P < .001) 16 …”
Section: Discussionmentioning
confidence: 99%
“…There are also other therapeutic options: laser hair combs (low‐level laser therapy), camouflage techniques, and surgical approaches including hair transplantation 11‐15 . Despite the success of approved therapies, commonly reported side effects and the need for continual use have led to the investigation of alternative therapies 16 . Consequently, there is an unmet need for new safe and effective agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation